Antimicrobial Resistance: Its Surveillance, Impact, and Alternative Management Strategies in Dairy Animals - Sharma, Chetan; Rokana, Namita; Chandra, Mudit; Singh, Brij Pal; Gulhane, Rohini Devidas; Gill, Jatinder Paul Singh; Ray, Pallab; Puniya, Anil Kumar; Panwar, Harsh (Frontiers in Veterinary Science, 2018)
Antimicrobial resistance (AMR), one among the most common priority area identified by both national and international agencies is mushrooming as a silent pandemic. The advancement in public healthcare through introduction of antibiotics against infectious agents is now being threatened by global development of multi drug resistant (MDR) strains. These strains are product of both continuous evolution and un-checked antimicrobial usage (AMU). Though antibiotic application in livestock has largely contributed towards health and productivity, however, has also played significant role in evolution of resistant strains. Although, a significant emphasis has been given to AMR in humans, trends in animals, on other hand are not much emphasized. Dairy farming involves surplus use of antibiotics as prophylactic and growth promoting agents. This non-therapeutic application of antibiotics, their dosage and withdrawal period needs to be re-evaluated and rationally defined. A dairy animal also poses a serious risk of transmission of resistant strains to humans and environment. Outlining the scope of the problem is necessary for formulating and monitoring an active response to AMR. Effective and commendably connected surveillance programs at multidisciplinary level can contribute to better understand and minimize the emergence of resistance. Besides, it requires a renewed emphasis on investments into research for finding alternate, safe, cost effective and innovative strategies, parallel to discovery of new antibiotics. Nevertheless, numerous direct or indirect novel approaches based on host-microbial interaction and molecular mechanisms of pathogens are also being developed and corroborated by researchers to combat the threat of resistance. This review places a concerted effort to club the current outline of AMU and AMR in dairy animals; ongoing global surveillance and monitoring programs; its impact at animal human interface; and strategies for combating resistance with an extensive overview on possible alternates to current day antibiotics that could be implemented in livestock sector.